Flying machine - Nahum, Andrew (New York : Knopf : Distributed by Random House, 1990)
A photo essay tracing the history and development of aircraft from hot-air balloons to jetliners. Includes information on the principles of flight and the inner workings of various flying machines.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Wilson's Children
Wilson's Junior High School
6.8
5-8
Keywords: Flying-machines -- Juvenile literature; Flying machines; Aeronautics -- History; Aeronautics -- History